Effect of Type of Flooring on Physiology and Skin Health of Murrah Buffalo Calves - Uppiretla, Tony; Kancharana, Ananda Rao; Peeka, Ashalatha; Regula, Vinoo; Mula, Ravi kumar; Allu, Teja (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Eighteen healthy Murrah buffalo calves of either sex aged 6-8 months, maintained at Buffalo Research Station (BRS), Venkataramannagudem, were randomly selected and housed in three separate pens for a period of 90 days, from August 2022 to October 2022. Calves of first group, second group and third groups were reared on concrete flooring (T1), Rubber mat flooring (T2) and soil floorings (T3), respectively. The overall mean rectal temperature (˚F) was significantly (P < 0.01) differed and followed a trend T3 < T1 < T2. The overall mean pulse rate and respiration rate were also differed significantly (P < 0.01) and followed a trend T3 < T2 < T1. The overall mean skin health score of T1 (1.52 ± 0.04) was significantly higher (P < 0.05) than T3 (1.29 ± 0.04) followed by T2 (1.36 ± 0.05) but there was no significant difference between T2 and T3. The overall mean heel erosions of T1 (0.64 ± 0.07) were significantly higher (P < 0.05) than T3 (0.33 ± 0.07) but doesn’t differ from T2 (0.48 ± 0.08) and there was no significant difference between T1, T2 and T2, T3. In the last fortnight, the average hoof concavity score of T1 (1.00 ± 0.01) was significantly higher (P = 0.05) than T3 (0.33 ± 0.21) but does not differ significantly from T2 (0.50 ± 0.22). In the last fortnight, the average hoof overgrowth score of T3 (1.00 ± 0.01) was significantly higher (P = 0.05) than T1 (0.33 ± 0.21) but doesn’t differ significantly from T2 (0.50 ± 0.22). From this it is concluded that rubber mats and soil flooring is better than concrete flooring as they maintain the vitals in normal range and cause less damage to the skin and hoof health.
Keywords: Flooring; Health; Murrah; Physiology